Study of Rhodotorula glutinis growth and lipid production using low cost substrates - Masih, Maj Neerja; Charles, E.S. (The Scientific Temper, 2016)
The present day challenge for biodiesel production is that as feedstock varied vegetable oils such as soybean oils, rap seed oils, palm oils and waste cooking oils are being used making it uneconomical. Microbial oil could represent an alternative to produce bio-oils for biodiesel production. In the present study in our lab red oleaginous yeast Rhodotorula glutinis was used for lipid production using various low cost substrates as sole carbon source. Rhodotorula glutinis culture was obtained from NCIM Pune and was subcultured and maintained on YPD medium. The growth conditions were optimised and dry cell weight and lipid content were estimated using fruit ,peel and sugar cane residue hydrolysate. The study can be further extended using different other substrates and result in cost effective high density cell culture.